STRATEGI PEMASARAN PENGELOLAAN LIMBAH MEDIS PADA PT. PRASADHA PAMUNAH LIMBAH INDUSTRI (PPLI): MARKETING STRATEGY ANALYSIS OF MEDICAL WASTE PT. PRASADHA PAMUNAH LIMBAH INDUSTRY ( PPLI ) - Harianto Harianto; Kirbrandoko Kirbrandoko; Imam Zulkarnain (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
According to the Indonesia Health Profile Information (http://kemenkes.go.id/) in 2018 reported estimates of the amount of medical waste that every day 2,820 hospitals in Indonesia are 230,840 kg per day. To date the best technology for treating and disposal medical waste is incinerators. In middle of 2019 PPLI decided to build an incinerator so that this was a new line of business for PPLI (Prasadha Pamunah Limbah Industri), this is very interesting when at one side PPLI is the big player in hazardous waste management but at another side PPLI is new comer for medical waste management, with the aim of analyzing the market at medical waste management service, identify of actors, factors and objectives that influence the medical waste management business. Through the swot analysis method it was found that PPLI was in quadrant 1, which means that PPLI has great strength and support from external side to succeed in medical waste management service business, which means PPLI facilities and services are complete so that mean PPLI can be the one company for Total Hazardous Waste Management in Indonesia. Keywords: hospital, medical waste, total hazardous waste management, PPLI, SWOT